Construction of Political Reality in The Caricature Entitled Qiblatul Maut and Ittabi'uni By Osamahajjaj: A Semiotic Study of Roman Jakobson - Jambak, Melinda Raswari; Rarasati, Indah; Hasanah, Ummi; Zawawi, Moh (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
بالرسم الكاريكاتوري نستطيع استنتاج الرسالة التي يرغب المؤلف في نقلها. هدف هذه الدراسة هو الكشف عن بناء الواقع السياسي الذي يريد أسامة حجاج أن ينقله في الكاريكاتير "قبلة الموت" و"اتبعوني". تستخدم هذه الدراسة نوعًا من البحث النوعي والأسلوب المستخدم هو أسلوب تحليل المحتوى. تتألف مصدر البيانات من مصدر بيانات أولية ومصدر بيانات ثانوية. المصادر الأولية هي كاريكاتورين من حساب أسامة حجاج على إنستغرام. بينما تتكون المصادر الثانوية من مقالات الأخبار والمجلات والكتب ذات الصلة بالدراسة. تم جمع البيانات من خلال الملاحظة العميقة للكاريكاتيرات، ثم سُجِّلت المسائل ذات الصلة بنظرية سيميائية لرومان ياكوبسون. يتم تحليل البيانات في ثلاث مراحل، وهي تقليل البيانات، وعرض البيانات، والاستنتاجات. نتائج البحث هي: (1) شكل بناء الواقع السياسي في صورة انتقاد سياسي لجو بايدن ومحاولة للسخرية من الولايات المتحدة التي تدعم حكومة إسرائيل، (2) يفي كاريكاتير أسامة المعنون "قبلة الموت" و"اتبعوني" بتحليل سيميائي رومان ياكوبسون في شكل المرسل، المستقبل، الرمز، الاتصال، السياق، والرسالة. In a caricature we can conclude a Message the author wants to convey. The purpose of this study is to reveal what are the constructions of political reality that Osama Hajjaj intends to convey in caricatures " قبلة الموت" and “اتبعوني”. This research uses a type of qualitative research, and the method used is content analysis. A data source consists of a primary data source and a secondary data source. The primary data sources are two caricatures from Osama Hajjaj's Instagram account. While secondary data sources consist of news articles, journals, and books relevant to the study. Data were collected through in-depth observation of caricatures, and then matters relevant to Roman Jakobson's semiotic theory were recorded. Data analysis is carried out in three stages: data reduction, data exposure, and conclusions. The results of the research are (1) the form of political reality construction in the form of political criticism of Joe Biden as well as an attempt to satirize the United States, which is pro with the Israeli government, (2) Osama's caricature entitled " قبلة الموت" and “اتبعوني” meets Roman Jacobson's semiotic analysis content in the form of addresser, addresse, code, contact, context, and message.